Gambaran Pengelolaan Arsip Di Sub Bagian Tata Usaha BLUD Rumah Sakit Umum Kota Banjar Tahun 2021: Overview of Archive Management in the Sub-Division of Administration of the Banjar City General Hospital BLUD in 2021 - Nursukma, Bulan Permata (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: In achieving the goals of government or private organizations, it is very necessary to manage administrative activities in an orderly and orderly manner, one of the activities in the Administrative Section is archival activities. The role of archives is very important in organizational activities as a center of memory and a source of information. Similar to records stored and managed by hospitals, hospital records are created along with the many activities carried out. Methods: The purpose of this study was to find out the description of archive management in the BLUD Administration Sub-Division of Banjar City General Hospital in 2021. This study used descriptive research methods and used a qualitative approach, using research instruments in the form of interviews, observations, and documentation. Results: Results of the study show that there are 3 human resources in the Administration Sub-Section, each of which has a role as the Head of the Sub-Division, Administration, and Archives. The archival facilities used are quite complete and adequate, and the archive management process has mostly been carried out in accordance with the regulations and procedures in the hospital. Discussion: It can be concluded that the management of archives in the Administrative Sub-section of General Hospital Banjar City is quite good, seen from all components supporting the needs of the Banjar City General Hospital Administration Sub Division. The Administrative Sub-Section needs to maximize the use of storage racks, and use electronic archive storage as a whole, it is necessary to create or create an archive borrowing control card, and archive management employees need to review the destruction of archives in accordance with applicable guidelines so that archive destruction can be carried out.